EXAFS Peaks and TPR Characterizing Bimetallic Interactions: Effects of Impregnation Methods on the Structure of Pt-Ru/C Catalysts - Nan-Yu Chen; Ming-Chun Liu; Shih-Chieh Yang; Jen-Ray Chang (Journal of Spectroscopy)
To investigate bimetallic interactions, Pt-Ru/C catalysts were prepared by coimpregnation (Pt-Ruco/C) and successive impregnation (Ru-Ptse/C), while Pt/C, Ru/C, and reduced Pt-Rublack were used as reference. Those samples were characterized by XAS and TPR. When Pt(absorber)-Ru(backscatter) phase-and-amplitude correction is applied to Fourier transformed (FT) EXAFS of Pt-Rublack at Pt edge, the characteristic peak of Pt-Ru interactions appears at 2.70 Å´, whereas, when Pt-Pt correction is applied, the peak appears at about 2.5 Å´. Detailed EXAFS analysis for Pt-Ruco/C and Pt-Ruse/C confirms the nature of the characteristic peak and further indicates that the interactions can semiquantitatively be determined by the relative intensity between Pt-Ru and Pt-Pt characteristic peaks. This simple method in determining bimetallic interaction can be extended to characterize Pt-Pd/γ-Al2O3. However, for Pt-Re/γ-Al2O3, Pt-Re interactions cannot be determined by the method because of the overlap of Pt-Pt and Pt-Re characteristic peaks due to similar phase functions.